Ikebana: An Ancient Tradition of Contemporary Healing and Artful Practice - Jennifer Fortuna (Scholarworks @ WMU, 2021)
Dr. Ricardo Carrásco, PhD, OTR/L, FAOTA, is an occupational therapy professor and ikebana artist. He provided the cover art for the Summer 2021 edition of The Open Journal of Occupational Therapy (OJOT). Ikebana is the ancient Japanese art of arranging flowers. "Kanta of the Wind, Sun and Moon" is an ikebana design made from blue and white Phalaenopsis orchids, chrysanthemum, bear grass, and heirloom driftwood. This gendaika, or freestyle design, is a haiku tribute to the wind, sun, and moon. Dr. Carrásco has been practicing occupational therapy and ikebana for more than 5 decades. As an occupational scientist and therapist, he has experience working in pediatric, academic, research, mental health, and wellness practice settings. Dr. Carrásco currently serves as headmaster of the Banmi Shofu Ryu school of ikebana. His story is shared from a sense of duty and obligation to preserve this ancient tradition of contemporary healing and artful practice.